2022
DOI: 10.1155/2022/3711371
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acid Regulation of the NLRP3 Inflammasome via the TLR4/NF-κB Signaling Pathway Affects Chondrocyte Pyroptosis

Abstract: Dietary fatty acid (FA) content and type have different effects on obesity-associated osteoarthritis (OA), but the mechanisms underlying these differences are not fully understood. Inflammation activated by toll-like receptor 4 (TLR4)/nuclear factor- (NF-) κB signaling and pyroptosis induced by the NLRP3/caspase-1/gasdermin D (GSDMD) signaling pathway play important roles in OA development. Our aim in this study was to observe the effects of dietary FAs on the articular cartilage of obese post-traumatic OA mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…90,91 It is believed that activation of the NLRP3 inflammasome occurs in two sequential steps -first, it must be primed, and then it can be activated. 71 When the body suffers from inflammatory disease, damage-associated molecules directly engage TLR4 and then quickly activate the NF-κB signaling pathway, resulting in augmented expression of NLRP3; [92][93][94] this in turn generates inflammatory cytokines such as IL-1β, IL-18, TNF-α and transforming growth factor-beta (TGF-β) which aggravate inflammation. 95 Some studies have found that SIRTs, especially SIRT1 and SIRT3, act on NLRP3 to exert anti-inflammatory functions.…”
Section: The Regulatory Role Of Sirts In Cellular Biologymentioning
confidence: 99%
“…90,91 It is believed that activation of the NLRP3 inflammasome occurs in two sequential steps -first, it must be primed, and then it can be activated. 71 When the body suffers from inflammatory disease, damage-associated molecules directly engage TLR4 and then quickly activate the NF-κB signaling pathway, resulting in augmented expression of NLRP3; [92][93][94] this in turn generates inflammatory cytokines such as IL-1β, IL-18, TNF-α and transforming growth factor-beta (TGF-β) which aggravate inflammation. 95 Some studies have found that SIRTs, especially SIRT1 and SIRT3, act on NLRP3 to exert anti-inflammatory functions.…”
Section: The Regulatory Role Of Sirts In Cellular Biologymentioning
confidence: 99%
“…Both loganin and morroniside have been confirmed to reduce chondrocyte pyroptosis and inflammation response through inhibiting activation of NF‐κB 84,85 . Study found that a diet rich in unsaturated fatty acids can play an anti‐inflammatory and anti‐pyroptotic effect to alleviate OA by inhibiting TLR4/NF‐κB axis and NLRP3/caspase‐1/GSDMD axis 171 . Moreover, hypoglycemic agent metformin reduced chondrocyte pyroptosis in an OA rat model by inhibiting NLRP3 172 .…”
Section: Pyroptosismentioning
confidence: 94%
“…84,85 Study found that a diet rich in unsaturated fatty acids can play an anti-inflammatory and anti-pyroptotic effect to alleviate OA by inhibiting TLR4/NF-κB axis and NLRP3/caspase-1/GSDMD axis. 171 Moreover, hypoglycemic agent metformin reduced chondrocyte pyroptosis in an OA rat model by inhibiting NLRP3. 172 Mesenchymal stem cell-derived exosomes, micro-RNAs, phytochemical, growth factors, biological enzymes, and exercise all exhibit good potential to inhibit chondrocyte pyroptosis.…”
Section: Pyroptosis In Oamentioning
confidence: 99%
“…This indicates that IRAK4 can act through the activation of NF-κB. NF-κB can promote the transcription of NLRP3, leading to the occurrence of pyroptosis [17]. NF-κB is involved in the pathophysiology of various central nervous system diseases, including epilepsy [18] and brain hemorrhage [19].…”
Section: Introductionmentioning
confidence: 99%